184k views
2 votes
(a³b¹²c²) × (a³c²) × (b³c¹) ⁰ =

12.4
O A. a¹5¹24
○ в. a³b¹¹c³
8
O c. a³b¹²4
OD. a¹4b¹5c9

(a³b¹²c²) × (a³c²) × (b³c¹) ⁰ = 12.4 O A. a¹5¹24 ○ в. a³b¹¹c³ 8 O c. a³b¹²4 OD. a-example-1
User Nadh
by
5.6k points

1 Answer

4 votes

Answer:

Explanation:

  • keep in mind that any number to the power 0 is equal to 1 therefore if you check carefully in the expression you will find that
    (b^(5) c^(4) )^(0) =1
  • And you should be able to know and apply the rules of exponents
  • but in this case the only one to be applied is :if you are to are multiplying powers of the same base add the exponents.

  • =a^(3) *a^(5)* b^(12) *c^(2) *c^(2)\\\\= a^(3+5) *b^(12) *c^(2+2)\\ =a^(8)b^(12) c^(4)
  • OPTION C IS the correct answer

User Somedotnetguy
by
5.3k points